Production Of Dried Grape Products Technological Evaluation of Kishmish - Mirzahidov Bakhtiyor; Mirzahidov Ulugbek (Genius Journals, 2022)
The article describes the research material on the topic “Production of dried grape products and technological assessment of Kishmish”. The research was carried out at the central experimental base of the Scientific-esearch Institute of Horticulture, Viticulture and Winemaking named after Academician M.Mirzaev Samarkand ScientificResearch Experimental Station, a technological assessment of dried products has been provided on 16 new varieties and hybrids of grapes. Drying of grapes has been carried out by the “Oftobi", “Soyaki” and “stacking" methods. The data on berries sugar content of fresh grapes in percents have been obtained. The duration of drying is establisd in days and the output of finished products in percent. Mechanical analyzes of dried grape berries have been carried out, the average weight, size and volume of 100 berries have been determined. A tasting assessment of dried grapes has been provided according to a 10-point system. The dried grapes biochemical composition on 8 varieties has been provided. Invert sugar and titratable acidity has been determined.
Keywords: Grapes; selection; seedlessness; variety